PENGARUH FASILITAS BELAJAR TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA ISLAM PESERTA DIDIK KELAS VIII DI SMPN 1 TELUKJAMBE BARAT - Wulandari, Elisa; Iqbal Amar Muzaki; M. Makbul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of learning facilities on the learning outcomes of Islamic Religious Education (PAI) among eighth-grade students at SMPN 1 Telukjambe Barat. This research employed a quantitative approach with a survey method. The population consisted of all eighth-grade students totaling 235 students, with a sample of 148 students determined using the Slovin formula and the Simple Random Sampling technique. Data were collected through questionnaires and documentation. Data analysis was conducted using IBM SPSS Statistics 26, including validity testing, reliability testing, descriptive statistical analysis, normality testing, linearity testing, and regression analysis through curve estimation. The results showed that learning facilities were in the moderate category with a percentage of 72%. The learning outcomes of Islamic Religious Education were also in the moderate category with a percentage of 61%. The regression analysis indicated that learning facilities did not have a significant effect on PAI learning outcomes, with a significance value of 0.099 (>0.05) and a coefficient of determination (R Square) value of 0.021. This indicates that learning facilities contribute only 2.1% to learning outcomes, while 97.9% are influenced by other factors such as learning motivation, the role of teachers, family environment, learning interest, learning media, and student discipline. Therefore, learning facilities are not the main factor influencing PAI learning outcomes among eighth-grade students at SMPN 1 Telukjambe Barat.